A bi-polyoxometallate-based host–guest metal–organic framework. Issue 16 (31st January 2020) - Wang, Sa-Sa; Yang, Wen-Bin; Yang, Mingxue; Wu, Xiao-Yuan; Wu, Weiming; Wang, Song-Xia; Lin, Lang; Lu, Can-Zhong
Abstract : An unprecedented bi-POM-based host–guest MOF with ultrahigh stability was synthesized, affording a new absorber for water harvesting from air. Abstract : Anionic POMs prefer to bond with positive metal cations instead of neutral or negative organic ligands. Therefore, it is challenging to synthesize POM-based MOFs, let alone bi-POM-based host–guest MOFs. In this work, an unprecedented bi-POM-based host–guest MOF, Na[Ni(enMe)2 ]4 [Ni(enMe)2 (H2 O)2 ]2 [Ni6 (μ3 -OH)3 (enMe)3 (SIP)1.5 (B-α-PW9 O34 )]2 [H3 PNiW11 O40 ]·5enMe·33H2 O (1 ), with Ni6 -capped [PW9 O34 ] as the node of the host framework and Keggin-type [PNiW11 O40 ] units as the guest was synthesized. 1 showed excellent chemical stability towards aqueous solutions of pH 2–12 at both ambient and boiling temperature, providing opportunities for its application in fresh water harvesting from air.